Optimal compensation method for centrifugal impeller considering aerodynamic performance and dimensional accuracy - Tao Zhou; Sitong Xiang; Hainan Zhang; Jianguo Yang (Alexandria Engineering Journal)
Impellers are crucial components in centrifugal compressors, and their precision and performance determine the compressor’s work efficiency. The traditional impeller error compensation method only compensates for dimensional errors without considering aerodynamic performance, which leads to a performance loss after compensation. This study proposes a novel optimal compensation method for centrifugal impellers that comprehensively considers the aerodynamic performance and dimensional accuracy. First, a nonlinear mapping relationship between the key geometric parameters of the blade and the aerodynamic performance was established. Then, using on-machine measurement data, the impeller machining error was calculated, and a mirror compensation surface was generated. Finally, based on the mapping model, the second-generation non-dominated sorting genetic algorithm was used to optimize the control points of the mirror compensation surface, and thereby obtain the optimal compensation surface. The experimental results showed that, after optimal compensation, the impeller dimensional error was reduced by 90.17 %, the total pressure ratio increased by 2.89 %, and the isentropic efficiency increased by 7.29 %. Compared to the traditional mirror compensation method, the dimensional accuracy, total pressure ratio, and isentropic efficiency were improved by 28.57 %, 1.56 %, and 4.24 %, respectively. Therefore, this compensation method can simultaneously improve the dimensional accuracy and aerodynamic performance of impellers.